Improvement of transmission line circuit on lossy substrate with application on phase shifter design - Pakasiri, Chatrpol; Kongchayasukwat, Thitipun (My University, 2019)
Lumped transmission line circuit design on lossy substrate is studied in this paper. Conventional single section lumped transmission line cannot perform well on lossy substrate as its electrical length gets longer. Multi-section transmission lines can be used to improve transmission line properties in this case. Phase shifter circuits are designed with a large electrical length transmission line. By using a multi-section transmission line, the resulting transmission line properties are better than those of single section transmission line.
Keywords: Lossy substrate; Lumped transmission line; Multi-section transmission line; Phase shifter